Participation of knowledge workers at the implementation of projects in Polish enterprises = Udział pracowników wiedzy przy realizacji projektów w polskich przedsiębiorstwach - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
For countries of contemporary world which are functional in the global economy, more and more a vision of carrying existing economic assumptions on based on assumptions associated with current functioning is becoming fleeting. Accessing the sustainable development to the route by creating more flexible organizational structures to market hesitations, in the support can turn out to be getting out of such an impasse for many enterprises about high special human capital.
Keywords: projekt; zarządzanie projektami; kierownik projektu; zespół projektowy; pracownik wiedzy; project; project management; project manager; team of project; knowledge worker